Antimicrobial susceptibility of bacteria isolated from neonatal foal samples submitted to a New Zealand veterinary pathology laboratory (2004 to 2013). Issue 2 (3rd March 2016) - Toombs-Ruane, LJ; Riley, CB; Kendall, AT; Hill, KE; Benschop, J; Rosanowski, SM
Abstract: AIMS: To describe antimicrobial susceptibility, and identify antimicrobial resistance (AMR), in bacteria isolated from New Zealand foals. METHODS: A database search was performed of submissions to a veterinary pathology laboratory between April 2004 and December 2013 for bacterial culture of samples from foals <3 weeks of age. Culture and susceptibility results were compiled with demographic information. Susceptibility results were as defined for the Kirby-Bauer disk diffusion susceptibility test based on Clinical Laboratory Standards Institute guidelines. Multi-drug resistance (MDR) was defined as non-susceptibility to ≥3 of a panel of antimicrobials (ceftiofur, enrofloxaxin, gentamicin, penicillin, tetracycline, trimethoprim-sulfonamide); penicillin susceptibility was not included for Gram-negative isolates. RESULTS: Submissions from 102 foals were examined, and 127 bacterial isolates were cultured from 64 (63%) foals. Of the 127 isolates, 32 (25%) were Streptococcus spp., 30 (24%) were Staphylococcus spp., 12 (10%) were Enterococcus spp. and 26 (21%) were Escherichia coli . Of 83 Gram-positive isolates, 57 (69%) were susceptible to penicillin. Over all isolates, 92/126 (73%) were susceptible to gentamicin and 117/126 (93%) to enrofloxacin; 62/82 (76%) of Gram-positive, and 22/42 (52%) of Gram-negative bacteria were susceptible to ceftiofur; 53/81 (65%) of Gram-positive, and 23/44 (52%) of Gram-negative bacteria were susceptible to tetracycline; 59/82 (72%) of Gram-positive, and 23/44 (43%) of Gram-negative bacteria were susceptible to trimethoprim-sulfonamide. Of 126 isolates, 33 (26%) had MDR; >1 isolate with MDR was cultured from 24/64 (38%) foals, and ≥2 isolates with MDR were recovered from 8/64 (13%) foals. CONCLUSIONS: Multi-drug resistance, including resistance to commonly used antimicrobials, was found in bacterial isolates from foals in New Zealand. CLINICAL RELEVANCE: The results of this study are of concern from a treatment perspective as they indicate a potential for antimicrobial treatment failure. For future surveillance of AMR and the creation of national guidelines, it is important to record more data on samples submitted for bacterial culture.